The Effect of Teaching Factory-Based Learning Method on the Industrial Chemistry Course - Fuadaturrahmah, Fuadaturrahmah (Education Achievement: Journal of Science and Research, 2024)
This study aims to examine the effect of the Teaching Factory-based learning method on students' understanding in the Industrial Chemistry course. The Teaching Factory method is a learning approach that integrates industrial practical experience with the theory taught in class, allowing students to acquire skills relevant to the workforce. This study uses an experimental design with two groups: the experimental group, which follows the Teaching Factory-based learning method, and the control group, which follows the conventional learning method. Data were collected through pre-tests and post-tests to measure students' understanding. The results show that the experimental group, which followed the Teaching Factory method, experienced a significant improvement in understanding, with an average difference in pre-test and post-test scores of 19.80 (p-value = 0.000), while the control group only showed a small improvement with a score difference of 5.85 (p-value = 0.020). Practical observation indicated that students in the experimental group were more skilled in performing industrial process simulations compared to the control group. Additionally, the results of the questionnaire showed higher satisfaction levels in the experimental group (average score of 4.2) compared to the control group (average score of 3.4). Based on these results, it can be concluded that the Teaching Factory-based learning method has a positive and significant impact on improving students' understanding in the Industrial Chemistry course and the practical skills relevant to the industrial world. This study recommends implementing this method more widely in higher education, especially in courses directly related to industrial processes.